GTS-12 adjusted age models for ODP Site 113-690 - Alexandra Auderset; Simone Moretti; Björn Taphorn; Pia-Rebecca Ebner; Emma Kast; Xingchen Wang; Ralf Schiebel; Daniel M Sigman; Gerald H Haug; Alfredo Martínez-García (PANGAEA, 2022)
GTS-12 timescale adjusted age models for ODP site 690 with biostratigraphic (calcareous nannoplankton and foraminifer) and magnetostratigraphic datums.
In: Auderset, A et al. (2022): Cenozoic foraminifera-bound nitrogen isotope records, TEX86-derived global SST compilation, and GTS-12 adjusted age models from multiple ODP/DSDP sites [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.943130